Active control of adaptive thin-walled beams incorporating bending-extension elastic coupling via piezoelectrically induced transverse shear. (January 2020) - Wang, Xiao; Song, Laishou; Xia, Pinqi
Abstract: Problems related to mathematical modeling and active control of adaptive composite thin-walled beams incorporating lateral bending-extension elastic coupling and piezoelectrically induced transverse shear-extension actuation coupling are considered. The adaptive capabilities are provided by anisotropic piezo-actuators embedded into the host structure. Based on classical negative velocity feedback control and linear-quadratic regulator optimal control, the control authority played by the directionality property of piezo-actuators on vibration suppression is discussed, considering in conjunction with that of the structural tailoring. The results show that the control strategy based on the piezoelectrically induced transverse shear-extension coupling can be more efficient than that based on the piezoelectrically induced bending. In addition, the control effectiveness based on the piezoelectrically induced transverse shear is sensitive to the bending-extension elastic coupling. Highlights: Active control via piezoelectrically induced transverse shear is feasible. Active control via transverse shear may make the system divergence. Control effectiveness of transverse shear is sensitive to elastic coupling. Piezo-actuator location has a significant effect on control authority.